2015
DOI: 10.1016/j.actamat.2015.06.035
|View full text |Cite
|
Sign up to set email alerts
|

On the mechanistic basis of fatigue crack nucleation in Ni superalloy containing inclusions using high resolution electron backscatter diffraction

Abstract: This is an authors' copy of a manuscript published in Acta Materialia Volume 97, 15 September 2015, Pages 367-379. http://dx.doi.org/10.1016/j.actamat.2015.06.035 AbstractA series of interrupted three-point bend low-cycle fatigue tests were carried out on a powder metallurgy FHG96 nickel superalloy sample containing non-metallic inclusions. High resolution electron backscatter diffraction (HR-EBSD) was used to characterize the distribution and evolution of geometrically necessary dislocation (GND) density, res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 73 publications
(36 citation statements)
references
References 59 publications
2
34
0
Order By: Relevance
“…This GND accumulation is partly due to the shape and sharp edges of carbides, see carbide 10,12,20 in Fig. 9b.…”
Section: Specimensmentioning
confidence: 99%
See 2 more Smart Citations
“…This GND accumulation is partly due to the shape and sharp edges of carbides, see carbide 10,12,20 in Fig. 9b.…”
Section: Specimensmentioning
confidence: 99%
“…and LCF crack initiation and propagation in inclusion-containing superalloys [19,20]. According to Stroh [32], the dislocation pile-up leads to crack nucleation as they increase the local shear stress which facilitates nucleation of a micro-cracks.…”
Section: On the Role Of MC Carbides And Mc Oxide In Lcf Deformation Mmentioning
confidence: 99%
See 1 more Smart Citation
“…Accumulated slip, for example, was found to be suitable in one study [36]. However, a range of recent work [4,14,27,29,31,37] in nickel and other alloys addressing fatigue crack nucleation utilising high resolution DIC and EBSD has demonstrated that quantities including local stress, accumulated slip (within PSBs), and GND density are necessary but not sufficient indicators of fatigue crack nucleation. While one or more of these quantities is usually associated with the site of defect nucleation, any one of them is not in its own right predictive.…”
Section: Stored Energy Density Criterion For Fatigue Crack Nucleationmentioning
confidence: 99%
“…32,33 The initial dislocation density was low and homogeneously distributed through the microstructure, and the presence of residual stress gradients was low. 31 After two cycles, the GND density and residual stress gradient ''hot spot'' (red) maps are shown in Fig. 5, where points from the top 5% of GND density distribution from the entire map are overlaid on the EBSD image quality (IQ) map.…”
Section: Hr-ebsd Study Of Plasticity In Polycrystals Containing a Secmentioning
confidence: 99%